119k views
1 vote
Below is the graph of y = - x ^ 3 Translate it to make it the graph of y = - (x - 2) ^ 3 - 4 .

Below is the graph of y = - x ^ 3 Translate it to make it the graph of y = - (x - 2) ^ 3 - 4 .-example-1
User Wusher
by
5.1k points

1 Answer

6 votes

Given the graph of the function:


y=-x^3

In order to make it the graph of the function:


y=-(x-2)^3-4

Translate the graph by 2 units to the right and 4 units downwards.

The graph of both functions is shown below:

To create your graph, drag the slider from (0,0) to (2,-4).

Below is the graph of y = - x ^ 3 Translate it to make it the graph of y = - (x - 2) ^ 3 - 4 .-example-1
User Frntz
by
4.3k points